Allowing for detachment processes in market innovation. The case of short food supply chains. Issue 4 (4th July 2021) - Le Velly, Ronan; Goulet, Frédéric; Vinck, Dominique
ABSTRACT: The purpose of this paper is to study the place of detachment processes in market innovation. The authors draw on the case of short food supply chains, especially those established to provide local produce for mass catering. They characterise short food supply chains as "market innovations through withdrawal", i.e. market innovations aiming at detaching farmers and consumers from the middlemen of mainstream markets and reducing the number of food miles. They argue that detachment from mainstream market mediators generally calls for the creation of new mediators and highlight the difficulties of this agencing work. In line with research on path dependence, they also show that existing attachments may impede detachments. Finally, the authors show that short food supply chains combine the establishment of new detachments and new attachments, and the maintenance of pre-existing attachments and pre-existing detachments. They sum up this combination of processes with the term "quasi-detachment".